Isotherm Adsorption Properties of Carbon Particles Obtained from Soursop Peel - Sri Anggraeni, Asep Bayu Dani Nandiyanto, Risti Ragadhita, Zulfa Fathi Arinalhaq, Salma Rahmadianti, Yulian Putri Chandra Rizky, M. Roil Bilad (International Journal of Advanced Science and Technology, 2020)
Investigation of adsorption isotherms of carbon particles obtained from soursop peel was carried out using curcumin as an adsorbate solution. To ensure analysis of the adsorption process, three carbon particle sizes (i.e., 530, 250, and 75 μm) were used in the evaluation of the adsorption process. The adsorption process was done in the batch method under ambient temperature and constant pressure. The produced carbon particles were characterized by a digital microscope, a sieve test, and a fourier transform infrared technique. The results of the isotherm adsorption analysis were compared with the Langmuir, Temkin, Freundlich, and Dubinin Radushkevich models. The results confirmed that all particle sizes of carbon particles have well-correlated with all isotherm models. The Temkin adsorption isotherm model provides the best correlation for the adsorption process using 530-μm carbon particles and the Langmuir adsorption isotherm performed better for the adsorption using 250 and 75 μm carbon particles. The effect of mean particle size has been studied. The results showed that particle size is very important to predict the adsorption process, therefore it is very important to have a homogeneous particle distribution (size and shape) to determine adsorption properties. Keywords: adsorption isotherm, carbon, curcumin, particle size, soursop peel.